Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Booth, Brian (AAPS J, 2014)
In September 2013, the FDA released a draft revision of the Bioanalytical Method Validation (BMV) Guidance, which included a number of changes to the expectations for bioanalysis, most notably the inclusion of biomarker assays and data. To provide a forum for an open, inclusive discussion of the revised draft BMV Guidance, the AAPS and FDA once again collaborated to convene a two-and-a-half day workshop during early December 2013 in Baltimore, MD, USA. The resulting format embodied extensive open discussion and each thematic session included only brief, concise descriptions by Agency and industry representatives prior to opening the floor discussion. The Workshop was built around four thematic sessions (Common Topics, Chromatographic, Ligand-Binding Assays, and Biomarkers) and a final session with international regulators, concluding with a review of the outcomes and recommendations from the thematic sessions. This Workshop report summarizes the outcomes and includes topics of agreement, those where the FDA will consider the Industry’s perspective, and those where the workshop provided a first open dialogue. This article will be available to the bioanalytical community at http://www.aaps.org/BMV13.